Propolis improves pregnancy outcomes and placental oxidative stress status in streptozotocin-induced diabetic rats - Umar Zayyanu Usman; Ainul Bahiyah Abu Bakar; Mahaneem Mohamed (BMC, 2018)
Abstract Background This study assessed the effects of propolis alone or combined with insulin on maternal status, pregnancy outcomes and placental oxidative stress in streptozotocin-induced diabetic rats. Methods Forty female rats were randomly assigned into five groups (n = 8/group) i.e. non-DM (non-diabetes), DM (diabetes), DM + Propolis (diabetes on propolis orally); DM + Insulin (diabetes on insulin subcutaneously) and DM + Combined (diabetes on propolis and insulin) groups. Propolis and insulin were given at 300 mg/kg/day orally and 5.0 IU/kg/day subcutaneously, respectively, for 4 weeks. Results Fasting blood glucose, conception period, implantation losses, foetal blood glucose and placental oxidative stress markers such as malonaldehyde and protein carbonyl were significantly higher while maternal weight gain, foetal body weight and total antioxidant capacity were significantly lower in DM group compared with non-DM group. These changes were significantly improved in rats treated with propolis or insulin alone with greater significant effects in rats treated with both propolis and insulin. Conclusion This study may suggest the protective effects of propolis against DM-induced impaired pregnancy outcomes and placental oxidative stress with greater effects when combined with insulin.